Pengaruh Kualitas Pengguna Sistem Informasi Akuntansi Terhadap Kualitas Pelaporan Keuangan Pada PT. Semen Baturaja (Persero) Tbk. Pabrik Panjang Provinsi Lampung - Heri Muhammad Ramdan; Kusnadi Kusnadi; Muhammad Luthfi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2015)
Abstract. The objective of the study was to demonstrate empirical proof about the effect of quality ofinformation system user towards quality of financial reporting of PT. Semen Baturaja (LimitedLiability) Panjang Factory of Lampung Province. Research population consisted of branch head,coordinators and all employees involved in the use of accountancy information system at PT. SemenBaturaja (Limited Liability) Panjang Factory of Lampung Province amounting to 45 people. Analysiswas done through double linear regression with T Test and F Test.Partially, the result of study showed that education of user (X1), training of user (X2) and intensity ofuser (X3) did not affect quality of financial reporting at PT. Semen Baturaja (Limited Liability)Panjang Factory of Lampung Province. Meanwhile, top management support (X4) partially influencedquality of financial reporting at PT. Semen Baturaja (Limited Liability) Panjang Factory of LampungProvince. Simultaneously, quality of accountancy information system uscr consisting variables such asuser education, user training, user intensity, top management support influenced quality of financialreporting at PT. Semen Baturaja (Limited Liability) Panjang Factory of Lampung Province.